Shredded maize stems as an alternative substrate medium - Tzortzakis, Nikos G.; Economakis, Costas D. (My University, 2008)
There is increased interest in the use of mixes of inorganic and organic materials as substrates in soilless culture in greenhouses, especially in parts of the world where the mixtures have not been commonly used. The potential of different ratios of shredded maize (Zea mays L.) stems as organic media on nutrient uptake, and the performance of tomato (Lycopersicon esculentum Mill.), in soilless culture, were studied. Tomato plants, cv. Belladona, were grown over a five-month period in a closed soilless culture system on four different substrates (pumice alone, shredded maize stems alone, pumice mixed with 25% or 50% maize shredded stems) and in Nutrient Film Technique, in an un-heated glasshouse. The amount of nutrient solution absorbed increased in proportion to days following transplanting, and was in part dependent on the strength of radiation and night temperature after the middle stage of growth. Plants grown on pumice + 50% maize and maize alone had similar distributions of elemental nutrient uptake. Elemental content in fruit was different only for Mn, Cu, B and Na among substrates. The ratio of number of leaves/fruit produced, favored plants grown in pumice + 50% maize, but plants grown in maize produced the greater number of fruit and the least number of leaves. No regression was observed between numbers of fruit and mean fruit weight. As nutrient uptake increased so did water uptake, with plants grown on pumice having the greater water use efficiency. The addition of maize in different ratios (25-50%) in pumice may improve its properties as a substrate for tomato soilless culture. The ratio of 50% shredded maize stems mixed with pumice could be the optimum mix for protected tomato production under the prevailing local conditions.
Keywords: Lycopersicum esculentum; Maize; NFT; Nutrient uptake; Organic materials; Pumice; Soilless culture